2016
DOI: 10.1002/hipo.22577
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hippocampal response to endocannabinoids after exposure to severe stress

Abstract: Women are more vulnerable to stress-related mental disorders than men and the naturally occurring fluctuation in estrogen that occur across the estrus cycle can dramatically influence the pathophysiology observed following traumatic events. It has been demonstrated that the endocannabinoid (eCB) system could represent a therapeutic target for the treatment of post-traumatic stress disorder (PTSD) in males. The current study aimed to examine the effects of exposure to a traumatic event and acute enhancement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 51 publications
4
16
0
1
Order By: Relevance
“…Similarly, both cannabinoid drugs prevented the effects of shock and reminders on hippocampal and amygdala dependent processes. These findings are consistent with previous findings showing an increase in CB1r protein levels in the BLA and CA1 one week after exposure to the single prolonged stress model of PTSD (Zer‐Aviv & Akirav, ). Neumeister et al, () showed that PTSD was associated with CB1r upregulation in an amygdala‐hippocampal‐cortico‐striatal neural circuit in response to low anandamide levels.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similarly, both cannabinoid drugs prevented the effects of shock and reminders on hippocampal and amygdala dependent processes. These findings are consistent with previous findings showing an increase in CB1r protein levels in the BLA and CA1 one week after exposure to the single prolonged stress model of PTSD (Zer‐Aviv & Akirav, ). Neumeister et al, () showed that PTSD was associated with CB1r upregulation in an amygdala‐hippocampal‐cortico‐striatal neural circuit in response to low anandamide levels.…”
Section: Discussionsupporting
confidence: 93%
“…WIN and URB also prevented the shock and reminders induced increase in startle response. This corroborates with previous studies from our lab demonstrating that systemic administration of cannabinoids after exposure to a traumatic event prevented the development of stress-induced impairment in Ext as well as the increase in startle and anxiety levels (Ganon-Elazar and Akirav, , 2012Akirav, , 2013Korem and Akirav, 2014;Zer-Aviv and Akirav, 2016).…”
Section: Effects On Inhibitory Avoidance and Acoustic Startle Responsesupporting
confidence: 92%
See 2 more Smart Citations
“…Controls were given the vehicle (Veh) only. Drug doses were based on previous reports [6,21,22]. Shock, situational reminders (SRs), and extinction Rats were placed in an inhibitory avoidance apparatus (for details see [7]).…”
Section: Methods and Materials Subjectsmentioning
confidence: 99%